2014
DOI: 10.22260/isarc2014/0022
|View full text |Cite
|
Sign up to set email alerts
|

Towards Autonomous Robotic In-Situ Assembly on Unstructured Construction Sites Using Monocular Vision

Abstract: -Unlike robotics in the manufacturing industry, on-site construction robotics has to consider and address two unique challenges: 1) the rugged, evolving, and unstructured environment of typical work sites; 2) the reversed spatial relationship between the product and the manipulator, i.e. the manipulator has to travel to and localize itself at the work face, rather than a partially complete product arriving at an anchored manipulator. The presented research designed and implemented algorithms that address these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
4
0
2
Order By: Relevance
“…Another approach is to place one or several fiducial markers, such as ArUco (Garrido-Jurado et al, 2014, on the objects of the scene to facilitate their detection and fine localization in images. This method was successfully used in Feng et al (2014). It however is less flexible as it requires carefully positioning these markers on visible flat surfaces of the objects at well defined locations.…”
Section: Object Localization and Pose Estimationmentioning
confidence: 99%
“…Another approach is to place one or several fiducial markers, such as ArUco (Garrido-Jurado et al, 2014, on the objects of the scene to facilitate their detection and fine localization in images. This method was successfully used in Feng et al (2014). It however is less flexible as it requires carefully positioning these markers on visible flat surfaces of the objects at well defined locations.…”
Section: Object Localization and Pose Estimationmentioning
confidence: 99%
“…Existen sistemas robustos donde interactúan robots de 6 GDL, los cuales a su vez son integrados a una base con movimiento en tres ejes que ensamblan estructuras de ma-jetos (Bueno, Arteaga y Candea, 2013), así como ensamblar cada uno de estos en una estructura prediseñada (Feng et al, 2014;Feng et al, 2015).…”
Section: Sistemas Retroalimentados Y Algoritmos De Planificaciónunclassified
“…Fuente: Ajustado de (Feng et al, 2014) y (Kayser et al, 2018. ) así como una rotación en el eje z, la cual está asociada a la pinza.…”
Section: Trabajo Pesadounclassified
“…Research in architecture and digital fabrication investigates novel production techniques in which material behavior is linked to fabrication and assembly tasks [5]. Recently, it has been shown that robots bring new capabilities to construction sites, an uncontrolled environment full of uncertainties [3].…”
Section: Related Workmentioning
confidence: 99%